A conceptual paper for development of halal food service system in Thailand - Wannasupchue, Wannasiri; Othman, Mohhidin; Che Ishak, Farah Adibah; Ungku Zainal Abidin, Ungku Fatimah; Mohamad, Siti Fatimah (Asian Economic and Social Society, 2019)
Halal certification for food service establishments is crucial when marketing them to the global travelers since the demand for Halal establishments is increasing every day. Many food service establishments are trying to be Halal certified because stringent Halal certification processes could give these establishments a competitive advantage which will result in higher revenue. Thailand has been receiving a high revenue from tourism industry. Meanwhile the food and beverage were the top five sectors that contributed 448 billion baht to the GDP in 2015. By having Halal certification, restaurants will be ensured Food Quality Standards that will guarantee the hygienic condition through implementation of GMP (Good Manufacturing Practice) and Halal certification. Nevertheless, currently the numbers of Halal restaurants in some areas are less than 20 establishments. This is not enough for visitors who wanted to consume Muslim foods. The main aim of this paper is to provide a literature review on Halal certification, thus proposing the conceptual framework on the opportunities of developing Halal Food Service system in Thailand. Finally, the findings will also provide recommendations on how restaurants? operators should strategize their business and focus towards acquiring Halal certification. These efforts could also help to better understand the current situations and efforts that could be carried out by tourism promotions bodies to promote these Muslim friendly locations to Muslim tourists around the world.